Plan estratégico de la clínica de rehabilitación física EMOFIS de la ciudad de Babahoyo. - Ponce Flores, Dora Katiuska (2011)
One of the documents that integrate management efforts, with clear goals and objectives, openness and consensus among internal and external stakeholders, enabling the rehabilitation clinic EMOFIS meet their users to whom it owes its rationale, this is the Plan Strategic. Consequently rehab must implement the necessary services that users require, so that appropriate care, timeliness and quality, making the rehabilitation process becomes a competitive advantage Emofis clinic. With the implementation of the Strategic Plan will get better customer service, enhance brand, demonstrate greater efficiency in the administration of the Clinic for Rehabilitation and monitor the plan so that there is security in meeting their goals. In conclusion we know that every company is looking for strategies and policies that are most relevant, optimizing its resources and revenue, with the injection of substantial investment in advertising that can expand the horizon of business services. Finally as part of this investigation and to achieve efficient outcomes. It is recommended human talent effectively motivate the clinic, continued until the final stages of implementation and communication, and once implemented the plan routinely evaluate and update it to reflect the changes that are introduced in the company's strategies and the challenges posed by competition rehabilitative counterparts.